Demands for Education and Health and the Desire for Social Mobility in Rural China: Perspectives on Weak Consumer Motivation. (June 2019) - Wang, Zengwen; Liu, Xiaodi
This article presents an explanation to the paradox of why increased household incomes in rural areas in China are accompanied by decreased motivation for consumption. The empirical analysis shows a reduction in rural residents' consumer spending with the exception of spending on medical treatment and education. This effect is stronger in poor families or families with school-aged children. The authors argue that motivation for consumption has been sinking in rural areas in China because income inequality among the rural populations has stimulated spending on improving human capital to promote individual security and social mobility as a chance to squeeze into the middle class.